Struktur dan Fungsi Naratif Kalimat Majemuk dalam Sastra Anak “Putri Saljudan Tujuh Kurcaci”: The Structure and Narrative Function of Compound Sentences in the Children’s Story “Putri Salju dan Tujuh Kurcaci” - Mahirsah, Meyvia; Sawardi, F.X. (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2026)
This research explores the types, structures, and functions of compound sentences found in the children’s story “Putri Salju dan Tujuh Kurcaci”. Using a qualitative descriptive method and a content analysis approach, the study carefully examines the text through close reading and note-taking to identify sentences containing more than one clause. The analysis centers on classifying compound sentence types (coordinate, subordinate, and mixed), describing their syntactic structures, and interpreting how they work within the narrative. The results show that compound sentences appear frequently throughout the story and play a key role in maintaining the flow and coherence of events. Subordinate compound sentences are found to be the most dominant, serving not only to link ideas but also to create a smooth and engaging storytelling rhythm for young readers. What makes this study unique is its linguistic focus on a well-known children’s tale a text type that is often overlooked in syntactic research. The findings offer meaningful contributions to language and literature education by providing a practical model for syntactic analysis that can be used in classroom learning, particularly at the elementary and secondary levels. Ultimately, this research supports the integration of linguistic theory and literary text analysis, enriching teaching strategies and helping students build stronger language comprehension skills.